Compatibilidade entre prescrições de enfermagem e necessidades de cuidados dos pacientes - Faedda, Marília Silveira (2016)
Analyze the correlation between nursing prescriptions recorded in the files and patient care needs; investigate the correlation between the professional profile of nurses and agreement of requirements; and investigate the conception of nurses about the nursing prescription for hospitalized patients care needs and factors associated with this conformity. Methods: Descriptive study with quantitative and documentary approach performed in 20 inpatient units and two medical clinics, two surgical clinics and 16 specialized units of teaching hospital in a city of São Paulo State. Data collection was performed in the period from September 2013 to January 2014 and from February to June 2015. On the first stage was applied the new version of validated patient classification instrument and, investigated 380 nursing prescriptions at admission and hospital discharge. Later, the participants (N = 139) answered a semi-structured questionnaire. Results: It was found that 75% of items of nursing prescriptions were consistent with the actual care needs of patients and 35% of the needs identified at admission and 32.3% at hospital discharge were not related prescriptions. It was found a low correlation between the compatibility of the nursing prescription and professional profile. For 43 (30.9%) of nurses the nursing prescriptions are always aligned to care needs of patients. Eliminations and Body Care, Skin Care and Mucous membranes and Research and Monitoring areas were the most discussed. Conclusion: The nursing prescriptions are not being carried out, if at all, in line with the needs of patients. It is recommended the implementation of strategies aimed at improving the quality of prescriptions, among others, continued qualification programs and the systematic use of instruments for evaluating the patient's attention demand in relation to nursing.